2015
DOI: 10.3109/00498254.2015.1041181
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic properties of trifolirhizin, (–)-maackiain, (–)-sophoranone and 2-(2,4-dihydroxyphenyl)-5,6-methylenedioxybenzofuran after intravenous and oral administration ofSophora tonkinensisextract in rats

Abstract: 1. SKI3301, a standardized dried 50% ethanolic extracts of Sophora tonkinensis, contains four marker compounds (trifolirhizin, TF; (-)-maackiain, Maack; (-)-sophoranone, SPN, and (2-(2,4-dihydroxyphenyl)-5,6-methylenedioxybenzofuran, ABF), is being developed as an herbal medicine for the treatment of asthma in Korea. This study investigates the pharmacokinetic properties of SKI3301 extract in rats. 2. The dose-proportional AUCs suggest linear pharmacokinetics of TF, Maack, SPN and ABF in the SKI3301 extract in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…However, little information is yet to be reported on the C max values of SPN after oral administration of SPN. As stated in the Introduction, from our previous study, the C max of SPN was reported to be 13.1 ng/mL in rats after oral dosing of 12.9 mg/kg SPN in rats [8]. Thus, we investigated whether SPN affects the pharmacokinetics of diclofenac and 4 -hydroxydiclofenac, produced by hepatic CYP2C9 enzyme, in rats.…”
Section: Discussionmentioning
confidence: 92%
“…However, little information is yet to be reported on the C max values of SPN after oral administration of SPN. As stated in the Introduction, from our previous study, the C max of SPN was reported to be 13.1 ng/mL in rats after oral dosing of 12.9 mg/kg SPN in rats [8]. Thus, we investigated whether SPN affects the pharmacokinetics of diclofenac and 4 -hydroxydiclofenac, produced by hepatic CYP2C9 enzyme, in rats.…”
Section: Discussionmentioning
confidence: 92%
“…Inadequate podocyte autophagy has been observed in patients with diabetes mellitus and proteinuria [7]. Impaired autophagy activity leads to the pathogenesis of DN, and the recovery of autophagy activity may be a promising therapeutic target for DN [8]. In addition, apoptosis and oxidative stress are important biological mechanisms involved in the pathogenesis of DN.…”
Section: Introductionmentioning
confidence: 99%
“…Alkaloids are considered as the major bioactive and toxic components (He et al, 2019;Lu et al, 2014;Wang et al, 2017;You et al, 2020). Recently, more studies have confirmed that flavonoids may be one of the primary pharmacologically active and toxic constituents (Jang et al, 2015;Lee et al, 2015;Pan et al, 2016;Sasajima et al, 1978). Nevertheless, studies on S. tonkinensis often focus on alkaloids and less on other compounds.…”
mentioning
confidence: 99%